What to Expect When You're Expecting - Murkoff, Heidi Eisenberg; Mazel, Sharon; Lockwood, Charles J. (New York : Workman Publishing, 2016)
Offers advice, insight, and tips for moms and dads, discussing pregnancy and birthing practices, prenatal screenings, postpartum birth control, and nutrition.
Keywords: Pregnancy; Childbirth; Postnatal care